A content analysis of the future of tourism through the presidential state of the nation address in the Philippines (1987-2019). Issue 1 (26th August 2020) - Capistrano, Robert Charles; Notorio, Paul Anthony
Abstract : Purpose: This study aims to examine the underlying statements with regard to strategic directions and action programmes on tourism found in the state-of-the-nation address (SONA) speeches of six Philippine presidents – from 1987 to 2019. The researchers believe that president SONAs are usually reflective of their plans and are strong indicators of their interest, which could particularly influence the Philippine tourism planning and development. Currently, the lack of guidance in the theoretical framework and research discussion in exploring the Philippine tourism policy and development priorities using presidents' SONA speeches are found wanting. Scenario planning approach was used as a framework. Design/methodology/approach: Scenario planning approach requires inputs from an advisory group to create scenario drivers. As inputs, the presidents' SONA speeches were used in this study while the researchers assumed the role of scenario thinkers. The speeches were downloaded and imported into a qualitative data software. Through a series of text search with regard to strategic directions and action programmes on tourism, underlying statements were subjected to content analysis to create nodes. The nodes were used as the basis in creating scenario drivers, which became the basis in creating the model. The models underwent the following validation procedures: researcher, concept and literature review. Findings: Based on the data, there are three identified major drivers of the present and future of Philippine tourism; these are tourism policy, tourism development and prospects for the future (temporal element). It also indicates tourism development and temporal element as dominant, with very few on tourism policies. By combining the tourism policy and tourism development, the development of the tourism policy and development confluence model was created. Meanwhile, the addition of the temporal element provided a third scenario driver that led to the creation of the dimensions of tourism policy and development scenarios. Practical implications: The developed model can be adapted to many contexts that extend even outside of tourism. The public tourism offices, such as the department of tourism and the regional, provincial, city and municipal tourism offices, can use the model to help them prioritise tourism development programmes and lobby for tourism policy creation. Social implications: The model will significantly assist decision-makers and policymakers to be conscious in crafting and enacting their tourism plans and programmes. It presents tourism policy and tourism development as scenario drivers that are interrelated; hence, a mutual relationship between the executive and legislative sectors of the government can be expected. Originality/value: The study positions its originality and value in three areas: scenario planning, tourism future and president's interest in tourism. In terms of scenario planning, the study was able to present interaction among three scenario drivers compared to most models that only have two. In the area of tourism future studies, this study claims that qualitative historical data can also be used to predict future scenarios. Despite the limited literature examining the tourism interest of the top-level administration, using speeches made by head of state is found plausible to predict the future of Philippine tourism.